Volume 4: Heat Transfer; Electric Power; Industrial and Cogeneration 1998
DOI: 10.1115/98-gt-329
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Heat and Mass Transfer in a Rotating Ribbed Coolant Passage With a 180 Degree Turn

Abstract: Numerical results are presented for flow in a rotating internal passage with a 180 degree turn and ribbed walls. Reynolds numbers ranging from 5200 to 7900, and Rotation numbers of 0.0 and 0.24 were considered. The straight sections of the channel have a square cross section, with square ribs spaced one hydraulic diameter (D) apart on two opposite sides. The ribs have a height of 0.1D and are not staggered from one side to the other. The full three dimensional Reynolds Averaged Navier-Stokes equations are solv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…Shih and Sultanian [20], gave a review on computations of internal and film cooling in gas turbines. Rigby [21] used k-omega turbulence model with concentration on grid structure to describe heat transfer in a ribbed channel with 180 deg bend and showed reasonable agreement with experimental results of Park et al [22]. Prakash and Zerkle [23] performed a computation of rib-roughened rotating duct neglecting buoyancy-centrifugal effect.…”
Section: Introductionsupporting
confidence: 67%
“…Shih and Sultanian [20], gave a review on computations of internal and film cooling in gas turbines. Rigby [21] used k-omega turbulence model with concentration on grid structure to describe heat transfer in a ribbed channel with 180 deg bend and showed reasonable agreement with experimental results of Park et al [22]. Prakash and Zerkle [23] performed a computation of rib-roughened rotating duct neglecting buoyancy-centrifugal effect.…”
Section: Introductionsupporting
confidence: 67%
“…Ooi et al (2002) present predictions using a v 2 -f model on orthogonal inline ribs and found that the model performs better than the k-e and S-A RANS models. Rigby (1998) studied the heat and mass transfer in a two pass ribbed channel with a 180°turn using a modified version of MenterÕs SST model (Menter, 1992(Menter, , 1993. Both stationary and rotating cases were studied.…”
Section: Introductionmentioning
confidence: 99%
“…Other three-dimensional CFD studies with k-ω model have been made and the overall flow structure was predicted in good agreement to the experiments. However, the vortical structures and the heat flux were overestimated in the stationary case and in the rotating setup the simulations did underestimate the heat flux in comparison to experiments by Rigby [4].…”
Section: Introductionmentioning
confidence: 62%